Production of Fruits and Leafy Vegetables Solanum nigrum Linn under Different Shade Levels - Nani Yulianti; Edi Santosa; Anas Dinurrohman Susila (Department of Agronomy and Horticulture, IPB University, 2018)
Fruits and young shoot of Solanum nigrum Linn are harvested and consumed as indigenous vegetables by different Indonesian ethnics. Preharvest factors and harvesting methods to maximize the quality of S. nigrum produce is still unknown. In this study S. nigrum was grown in full irradiance and under shading and assessed for their growth, and fruit and shoot yields. The experiment was conducted at the Leuwikopo Experimental Farm in Bogor Agricultural University, Indonesia from April-July 2017. The results demonstrated that plants produced more fruits and shoots in full irradiance, i.e., 687.9 g and 211.1 g per plant, whereas only 331.1 g and 116.9 g per plant were produced in 50% shading. Although fruit and shoot production were superior under full irradiance, shoot-harvested plants had healthier leaves and life span of about 2 months longer thus facilitating longer availability. Canopy of shoot-harvested plants formed a columnar shape with 23 to 45 cm in height, in contrast to spherical shape with 48 to 203 cm in height of the fruit-harvested plants. It is likely that shading level might contribute to farmers’ decision to harvest the shoots or fruits of S. nigrum. Further studies are needed to determine the effects of shading levels on nutritional quality of the shoots and fruits of S. nigrum. Keywords: African nightshade, canopy architecture, harvesting method, indigenous vegetable, intercropping